Complications following reverse total shoulder arthroplasty for proximal humeral fractures: a systematic review - Easton J. Bents, BS; Javier Ardebol, MD; Mathew Noble, DO; Lisa Galasso, MD; Patrick J. Denard, MD; Mariano E. Menendez, MD (JSES Reviews, Reports, and Techniques)
Background: Reverse total shoulder arthroplasty (rTSA) is an increasingly common procedure for proximal humerus fractures (PHFs), but postoperative complications have not been well characterized. The purpose of this systematic review is to assess complications and revision rates following rTSA in the management of PHFs as documented in current literature. Methods: A systematic review was performed on primary rTSA for PHFs. In adherence to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic search was conducted between September and December of 2023, utilizing the databases PubMed, Scopus, and the Cochrane Library to include relevant articles from any period. A total of 102 studies were identified for inclusion after initial screening of 3800 query results. Extracted data from each article included the publishing journal, level of evidence, study design, number of patients, mean age, age range, percent female, mean follow-up, specific postoperative complications, total complications, complication rate, number of revisions, and revision rate. Overall complication rates were determined by dividing total complications by total patients and multiplying by 100, which also applied to revision rates. Results: Among 10,797 primary rTSA cases for PHFs identified from 102 studies, the mean age of patients was 75.6 ± 3.6 years, and 82.6% of patients were female. The average follow-up was 38.9 ± 21.0 months. The overall complication rate was 7.0% (754/10,797) with a range of 0% to 46.9%. The most common postoperative complications were prosthetic instability/dislocation (2.3%, 244/10,797; range: 0%-7%) and infection (1.2%, 131/10,797; range: 0%-2.5%). Periprosthetic fracture (0.8%), nerve injury (0.3%), and other complications were also documented. The overall revision rate was 3.3% (355/10,797; range: 0%-28%). Conclusion: This systematic review summarizes the most common postoperative complications of rTSA for PHFs. The most frequent complication was prosthetic instability/dislocation, followed by infection. While the average total complication and revision rates were relatively low, there was wide variability, with some studies reporting rates as high as 46% and 28%, respectively.